Prostate cancer cell‐intrinsic interferon signaling regulates dormancy and metastatic outgrowth in bone - Katie L. Owen; Linden J. Gearing; Damien Zanker; Natasha K. Brockwell; Weng Hua Khoo; Daniel Roden; Marek Cmero; Stefano Mangiola; Matthew Hong; Alex Spurling; Michelle M. McDonald; Chia‐Ling Chan; et al. (2020)
The latency associated with bone metastasis emergence in castrate-resistant prostate cancer is attributed to dormancy, a state in which cancer cells persist prior to overt lesion formation. Using single-cell transcriptomics and ex vivo profiling, we have uncovered the critical role of tumor-intrinsic immune signaling in the retention of cancer cell dormancy. We demonstrate that loss of tumor-intrinsic type I IFN occurs in proliferating prostate cancer cells in bone. This loss suppresses tumor immunogenicity and therapeutic response and promotes bone cell activation to drive cancer progression. Restoration of tumor-intrinsic IFN signaling by HDAC inhibition increased tumor cell visibility, promoted long-term antitumor immunity, and blocked cancer growth in bone. Key findings were validated in patients, including loss of tumor-intrinsic IFN signaling and immunogenicity in bone metastases compared to primary tumors. Data herein provide a rationale as to why current immunotherapeutics fail in bone-metastatic prostate cancer, and provide a new therapeutic strategy to overcome the inefficacy of immune-based therapies in solid cancers.